Conceptualization and mechanisms of digital citizen engagement in local development: from electronic participation to contractual-participatory relations. - Pupiаlis Yegor (Pressing Problems of Public Administration, 2025)
This article presents a comprehensive conceptual model for institutionalizing public administration of national security specifically adapted to address the multifaceted challenges of hybrid warfare. The research substantiates the critical necessity for fundamental transformation of traditional security institution approaches, demonstrating how sectoral specialization and rigid competency demarcation prove structurally inadequate when confronting complex multidimensional threats that systematically exploit inter-agency gaps and organizational fractures. The study develops an innovative multilevel integration model that synthesizes strategic, operational, and regional management levels through a systematic framework of foundational principles, architectural elements, and adaptive mechanisms. Thirteen core principles are proposed for constructing an integrated management system: systemic integrity, adaptive architecture, network-centricity, information integration, proactivity, distributed resilience, inclusiveness, continuity, technological innovation, strategic communication, legal legitimacy, continuous learning, and economic efficiency. These principles address specific vulnerabilities of fragmented security systems while ensuring operational effectiveness in dynamic threat environments. The architectural framework operates across three distinct levels, featuring an innovative functional cluster approach at the operational level that organizes related agencies under unified command structures. Key innovations include establishment of a National Resilience Center as an inter-agency coordination structure responsible for critical infrastructure protection and crisis management, alongside a network of Regional Security and Resilience Centers providing territorial coordination capabilities. This architecture maintains functional specialization while achieving deep institutional integration through horizontal networking mechanisms and shared information platforms. Critical adaptation mechanisms enable system evolution in response to hybrid threat dynamics through early weak signal detection systems, scenario-based forecasting methodologies, organizational flexibility protocols, and cognitive adaptability frameworks. The model incorporates advanced technological platforms including artificial intelligence analytics, quantum-secured communications, blockchain data integrity systems, and digital twin infrastructure modeling capabilities. The research demonstrates that this integrated approach generates synergistic effects exceeding the arithmetic sum of individual agency capabilities, while preserving essential functional autonomy and operational specialization. The model addresses the fundamental challenge of coordinating heterogeneous security components against multi-domain threats characteristic of contemporary hybrid aggression. Implementation requires not merely structural reforms but transformational changes in organizational culture, inter-agency trust development, and professional education approaches. The framework provides concrete architectural solutions for all management levels while maintaining sufficient flexibility for adaptation to evolving security environments and national contexts.